Uncover Potential Fraud and its Mitigation Efforts in the Assistant Corps - Miranda Dewina Hutapea; Aprina Nugrahesthy Sulistya Hapsari (Asia Pacific Fraud Journal, 2021)
This study aims to describe the potential for fraud in the operational activities of the Assistant Corps and explore the motives underlying the potential for fraud. The Assistant Corps is an organization that coordinates assistant lecturers and serves to coordinate assistant activities. This research is a qualitative descriptive study. The data in this study are primary data obtained through in-depth interviews with Assistant Coordinators, Active Assistants, Alumni of Assistant Coordinators, and Assistance Class Students. The results show that the Assistant Corps has three potential frauds that can occur both in operational activities and in financial management, namely misappropriation of assets, fraudulent statements, and corruption. The anti-fraud strategy implemented in this organization is inadequate and has a high risk of threatening the organization if it is not managed properly.